Glove Selection for Working with Pesticides - Frederick M. Fishel (EDIS)
This document explains how to select gloves suitable for handling pesticides. A chemical-resistance chart for various approved materials is presented, and examples of the types of available gloves are displayed. This document is PI-120, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date April 2006.